1985
DOI: 10.1287/inte.15.6.47
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Cost-Service Trade-offs on Industry Logistics Structures

Abstract: The characteristics of the technology and markets within an industry will affect the range of logistics systems observed in that industry. In some industries the range is wide, while in others all firms make the same logistics choices. This paper explores these differences. We propose the concept of an efficient frontier of cost-service choices and show how firms align themselves along the frontier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Third, more precise theories are needed to describe the structural and environmental contingencies which enhance compatibilities between competitive priorities (e.g. [ 39]).…”
Section: Research In Manufacturing Strategymentioning
confidence: 99%
“…Third, more precise theories are needed to describe the structural and environmental contingencies which enhance compatibilities between competitive priorities (e.g. [ 39]).…”
Section: Research In Manufacturing Strategymentioning
confidence: 99%
“…Further support for the existence of trade-offs between different performance areas was provided by Hayes and Wheelwright (1984), Richardson et al (1985), Rosenfield et al (1985), Fine and Hax (1985) and Wacker (1987). These authors refined Skinner's original ideas and identified the following main performance areas between which trade-offs might be expected to exist:…”
Section: Literature Reviewmentioning
confidence: 95%
“…In a make-to-stock industry, for example, the order-to-delivery time depends on the positioning of finished goods inventories in the logistics network and it is a criteria as important as cost for the evaluation of network designs. The non-dominated designs are located on an efficient-frontier^ and any of these designs could constitute a good solution for a firm (Rosenfield, 1985). Figure 9.1 illustrates the cost accumulation process and the impact of inventory positioning on customer delivery times for a simple multi-echelon (stage) supply chain.…”
Section: Performance Evaluationmentioning
confidence: 99%